Pengembangan Media Pembelajaran Smart Box pada Mata Pelajaran IPAS Materi Kegiatan Ekonomi Kelas V di SDN 24 Mataram - Huzaematul Huriah; Ida Ermiana; Muhammad Sobri (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to determine the feasibility, practicality, and effectiveness of the smart box learning media in the IPAS subject on economic activity material for 5th-grade students. This research uses the Research and Development method with the ADDIE development model (Analyze, Design, Development, Implementation, Evaluation). The subjects of this study were 5th-grade elementary school students totaling 13 students. Data collection techniques used questionnaires, observations, tests, and documentation. Validation results showed that the smart box media has a very high level of feasibility, with the feasibility percentage from media experts at 90% and material experts at 82%. The practicality result from student responses was 90%, which falls into the very practical category. Meanwhile, the effectiveness of the media is seen from the completeness of the students' learning test results after using the smart box media. As for the results of student learning mastery, it reached 92.3%, which falls into the very effective category because the smart box media developed in this study integrates concrete media with digital media and is equipped with interactive games that can increase students' motivation, activeness, and understanding of economic activity materials. Thus, it can be concluded that smart box learning media in the IPAS subject on economic activity materials is declared very feasible, practical, and effective for use in learning.